2016
DOI: 10.1111/iej.12665
|View full text |Cite
|
Sign up to set email alerts
|

Transdentinal photobiostimulation of stem cells from human exfoliated primary teeth

Abstract: Infrared LED irradiation was capable of biostimulating SHEDs through a 0.2 mm thickness of dentine, especially at the 4 J cm level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Moreover, red light is known to present less scattering and losses during its trajectory when compared with the blue light (Neupane et al, 2010). It can be suggested that during cell exposure to the blue LED, the light dissipation impaired reaching target cells effectively (Turrioni et al, 2016). Another parameter considered was the temperature change by light exposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, red light is known to present less scattering and losses during its trajectory when compared with the blue light (Neupane et al, 2010). It can be suggested that during cell exposure to the blue LED, the light dissipation impaired reaching target cells effectively (Turrioni et al, 2016). Another parameter considered was the temperature change by light exposition.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 78 human third molars were used after the approval from the Research Ethics Committee (CAAE 13072813.2.0000.5416) of the Araraquara School of Dentistry − UNESP. The teeth were cut and ground (Turrioni et al, 2016) to obtain dentin discs with a final thickness of 0.2 mm. The smear layer was removed by applying an EDTA 0.5 M (pH 7.2) solution for 30 seconds on both surfaces of the discs, and subsequent deionized water rinsing for 60 seconds.…”
Section: Dentin Discs and Measurement Of Led Light Attenuationmentioning
confidence: 99%
“…The irradiation of cultured pulp cells was performed using a LED table; this device is widely employed in laboratorial studies in this research field (Fig. 1) [2,22,23,[39][40][41]. The LED table was developed by the Optical Group (OG) of the Optics and Photonics Research Center (Centro de Pesquisa em Óptica e Fotônica -CePOF) of the São Carlos Institute of Physics (IFSC) at the University of São Paulo (USP).…”
Section: Irradiation Devicementioning
confidence: 99%
“…The potential beneficial parameters (4 J/cm 2 , 15 J/cm 2 , and 30 J/cm 2 at 0.04 W/cm 2 ) [20,23,30,39,40], as well as more intense parameters, which may be considered to be potentially harmful to the cells (4 J/cm 2 , 15 J/cm 2 , and 30 J/cm 2 at 0.08 W/cm 2 ), were assessed. The irradiation parameters used in this study are shown in Tables 2 and 3.…”
Section: Irradiation Devicementioning
confidence: 99%
“…Na tabela abaixo foram reunidos os principais substitutos cutâneos encontrados na literatura. , 2016a;DOURADO et al, 2015;FARFARA et al, 2015;TURRIONI et al, 2017;AHMED e SAYED, 2012;DAWOOD e SALMAN, 2013;NOVAES et al, 2014;MARTINS et al, 2017;ELSON e FORAN, 2015). Além disso, estudos apontam que esta modalidade possui efeitos celulares na proliferação de fibroblastos, matriz extracelular, produção de colágeno, formação do tecido de granulação e redução da resposta inflamatória, tornando-se uma terapia alternativa para os processos de cicatrização e reparação tecidual (DEYHIMI et al, 2016 Lubart e colaboradores estudaram a hipótese de que a fotobioestimulação poderia ser mediada pela produção de pequenas quantidades de espécies reativas de oxigênio e para tal, concentrações baixas de derivados de hematoporfirina foram adicionados às culturas de fibroblastos que foram irradiadas com laser de HeNe.…”
Section: 3-engenharia Tecidual E O Modelo Celular Tridimensional Deunclassified